Assessment of oro-motor functions and gross motor abilities in spastic cerebral palsy - Heba Khaire Mahmoud Abdullah; Asmaa Ahmed Abdelhamed; Eman Ibrahim Elhadidy; Gehan Mosaad Abdelmaksoud (Cairo : Heba Khaire Mahmoud Abdullah, 2020)
Background:The oral feeding and swallowing is complex and integrated function which is affected in most of cerebral palsy children and consider major risk factor of morbidity. Aim: to determine relation between oral motor functions and gross motor abilities in children with spastic CP and also to compare the oral motor functions among subtypes of spastic CP. Materials and Methods: One hundred children with different types of spastic CP participated in the study and their ages ranged from one to four years.The oral motor functions and gross motor abilities were evaluated using Schedule for Oral motor assessment (SOMA) and gross motor functional measure scale (GMFM) respectively. Results: There was direct positive correlation between total score of SOMA and total score GMFM. There were direct positive correlation between SOMA categories and GMFM, as between GMFM scale and puree, GMFM scale and semi-solids, GMFM scale and solid , GMFM scale and cracker , and GMFM scale and cup While no significant correlation between GMFM scale and bottle, GMFM scale and trainer-cup. There were differences in results of SOMA scoring in subtypes of CP Conclusion: There was a strong significant correlation between oral motor functions and gross motor abilities in children with spastic CP
Thesis (M.Sc. ) - Cairo University - Faculty of Physical Therapy - Department of Growth and Development Disorders in Pediatrics
Issued also as CD
Keywords: Cerebral Palsy; Gross Motor Abilities; Oral Motor